Best‐practices for preventing skin injury beneath personal protective equipment during the COVID‐19 pandemic: A position paper from the National Pressure Injury Advisory Panel. Issue 3 (13th June 2021) - Padula, William V.; Cuddigan, Janet; Ruotsi, Lee; Black, Joyce M.; Brienza, David; Capasso, Virginia; Cox, Jill; Delmore, Barbara; Holden‐Mount, Sarah; Munoz, Nancy; Nie, Ann Marie; Pittman, Joyce; et al.
Abstract: COVID‐19 has infected millions of patients and impacted healthcare workers worldwide. Personal Protective Equipment (PPE) is a key component of protecting frontline clinicians against infection. The benefits of PPE far outweigh the risks, nonetheless, many clinicians are exhibiting skin injury caused by PPE worn incorrectly. These skin injuries, ranging from lesions to open wounds are concerning because they increase the susceptibility of viral infection and transmission to other individuals. Early into the COVID‐19 pandemic (April 2020), the U. S. National Pressure Injury Advisory Panel (NPIAP) developed a series of position statements to improve wear‐ability of PPE and protect healthcare professionals and their patients as safe from harm as possible under the circumstances. The NPIAP positions, which were formed by conducting a systematic review of what was known at the time, include: (a) Prepare skin before and after wearing PPE with skin sealants, barrier creams and moisturisers; (b) Frequent PPE offloading to relieve pressure and shear applied to skin; (c) treat visible skin injuries immediately caused by PPE to minimise future infection; (d) non‐porous dressings may provide additional skin protection, but lack evidence; (e) health systems should take care to educate clinicians about placement and personal hygiene related to handling PPE. Throughout all of these practices, handwashing remains a top priority to handle PPE. These NPIAP positions provided early guidance to reduce the risk of skin injury caused by PPE based on available research regarding PPE injuries, a cautious application of evidence‐based recommendations on prevention of device‐related pressure injuries in patients and the expert opinion of the NPIAP Board of Directors. Clinicians who adhere to these recommendations reduce the prospects of skin damage and long‐term effects (e.g. scarring). These simple steps to minimise the risk of skin injury and reduce the risk of coronavirus infection from PPE can help.